Gender‐related cost discrepancies in a cohort of 110 facial moisturizers. (15th April 2019) - Manatis‐Lornell, Athena J.; Marks, Dustin H.; Hagigeorges, Dina; Okhovat, Jean‐Phillip; Senna, Maryanne M.
Abstract: Background: Gender‐related price inequalities for over‐the‐counter dermatologic products such as shampoos and conditioners, razors, deodorants, and lotions remain prevalent in the marketplace. This trend has also been found to apply to topical minoxidil, a common treatment for male and female pattern hair loss. Objective: We sought to identify the gender‐related price discrepancies of facial moisturizers, which are routinely recommended by dermatologists. Methods: Three online retailers (Amazon, Target, and Walmart) were surveyed for available facial moisturizers in October 2018. Facial moisturizers were classified as men's, women's, or gender‐neutral based on three specific marketing variables: language, container color/graphics, and container curvature/shape. Results: In total, 110 facial moisturizers were included in this analysis. Of the 54 facial moisturizers evaluated for men, 47 (87%) contained the word "men" within the marketing language, while only three of 56 (5.4%) facial moisturizers targeted at women were explicitly labeled "for women." No statistically significant difference was found between the number of facial moisturizers listed as fragrance‐free, SPF‐containing, anti‐aging, or those labeled as sensitive, hypoallergenic, or dermatologist recommended between the two groups. However, facial moisturizers marketed to women were on average 3.09 more per ounce than those marketed to men. A two‐tailed t test revealed a statistically significant difference between the price per ounce of facial moisturizers for men (6.20) and those for women (9.29) ( P = 0.013). Conclusion: Facial moisturizers marketed to women were found to be significantly more expensive than comparable facial moisturizers marketed to men.